Edukasi Rumah Sehat “Door To Door System” Meningkatkan Pengetahuan Sikap dan Perilaku Keluarga Penderita Tb Paru - Sudiadnyana, I Wayan; Yulianti, Anysiah Elly (Jurnal Skala Husada : The Journal of Health, 2025)
Background: Pulmonary TB disease is still a global health problem. Various prevention efforts have been made, but until now pulmonary TB disease has not been completely treated. Transmission of pulmonary TB disease is influenced by two dominant factors, namely the environment and behavior. The proposed study aims to measure the effectiveness of healthy home education "door to door system" in improving knowledge, attitudes and behavior of pulmonary TB prevention.Method: Pre-experimental research with pre and post-test design. The sample was a total population of 32 respondents of families with pulmonary TB.Result: Healthy home education can increase average knowledge before 7.8 and 14.0. Attitude before 5.5 and after 6.5. Behavior before 5.2 and after 5.8. The increase in knowledge reached 72.9%, attitude 18.3% and behavior 11.4%. Statistical tests showed that there was a difference in the average value of knowledge, attitude and behavior of preventing pulmonary TB before and after providing healthy home education, with a ρ value for knowledge: 0.000, attitude: 0.002 and behavior: 0.006.Conclusion: Healthy home education “door to door system” is quite effective to improve knowledge, attitude and behavior of families of patients in preventing pulmonary TB. The health center is advised that direct education “door to door system” be one of the alternative counseling activities to involve family participation in preventing pulmonary TB.